Trans-Regional Echoes of Resistance: A Sociolinguistic Reading of Gendered Agency in E. Rokajat Asura’s Raden Dewi Sartika and its Parallelisms in Acehnese Female Discourse - Ruth Angel Manurung; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2026)
The turn of the twentieth century in the Dutch East Indies was characterized by a rigid colonial diglossia and deeply entrenched indigenous patriarchal structures that severely gatekept formal education from women. While traditional scholarship evaluates early feminist movements through isolated socio-historical or biographical lenses, this study addresses a distinct research gap by exploring the trans-regional sociolinguistic dimensions of female resistance. The primary objective is to investigate how language variation, stratified honorifics, and institutional registers are deployed as instruments of defiance in E. Rokajat Asura’s biographical novel Raden Dewi Sartika, drawing conceptual parallelisms with historical Acehnese female discourse. Utilizing a qualitative literary-sociolinguistic framework grounded in Dell Hymes’ ethnography of communication and Mikhail Bakhtin’s heteroglossia, this research evaluates dialogue sequences and narrative prose at a fine granularity. The findings reveal that characters strategically manipulate formal, elite registers and indigenous honorific systems to maintain surface-level compliance while successfully executing subversive institutional demands. This micro-linguistic negotiation directly parallels the historical socio-political discourse of aristocratic female figures in Aceh who appropriated customary speech to command authority. Ultimately, this study demonstrates that early Indonesian female agency relied on the tactical mastery of existing linguistic hierarchies to subvert oppression. These insights offer a novel trans-regional model that enriches the academic understanding of language, gender, and institutional autonomy across the shared socio-cultural landscape of Aceh and the wider Indonesian archipelago.